2004
DOI: 10.1111/j.1524-6175.2004.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide Primary Care Approach to Cardiovascular Risk Factor Control in High‐Risk Diabetic and Nondiabetic Patients With Hypertension

Abstract: Patients with multiple cardiovascular risk factors benefit from having them all controlled, but this rarely occurs. Fifty-seven primary care providers were enrolled in a program to monitor cardiovascular risk factor control. Data were obtained on 7315 hypertensives. This analysis focuses on 3460 high-risk hypertensives including 2199 with diabetes and 1261 with clinical cardiovascular disease. Blood pressures were <140/90 mm Hg and <130/80 mm Hg in only 44.3% and 20.4% of diabetics and 49.6% and 26.6% nondiabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(47 reference statements)
3
24
0
1
Order By: Relevance
“…15,18 Similar to previous studies, our study also demonstrated that the blood pressure control was worse among diabetics and those with a high BMI. 16,17,21 In the multivariate analysis, the presence of concomitant CVD showed a negative association with high blood pressure, a finding being consistent with literature. 16 As with many countries, there are differences between geographic regions for the developmental level in Turkey, and the blood pressure control rate may vary between the geographic regions of Turkey and according to the status of socioeconomic level.…”
Section: Hypertension Control In Primary Caresupporting
confidence: 80%
“…15,18 Similar to previous studies, our study also demonstrated that the blood pressure control was worse among diabetics and those with a high BMI. 16,17,21 In the multivariate analysis, the presence of concomitant CVD showed a negative association with high blood pressure, a finding being consistent with literature. 16 As with many countries, there are differences between geographic regions for the developmental level in Turkey, and the blood pressure control rate may vary between the geographic regions of Turkey and according to the status of socioeconomic level.…”
Section: Hypertension Control In Primary Caresupporting
confidence: 80%
“…The patients reported a relatively healthy lifestyle, including physical exercises (71%), diet (75%), not smoking (89%) and not consuming alcohol (85%). In total, 30% of the study population were born in Israel, 32% were born in Europe or America, 20% in Asia and 18% in North Africa, The mean number of years of education was 13 (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean duration of diabetes was 6.6 years (range 1-23).…”
Section: Resultsmentioning
confidence: 99%
“…11,12 However, data show that only 44.3% achieve a BP o140/90 mm Hg and only 20.4% reach the recommended target of o130/80 mm Hg. 13 Compliance with drug therapies is compromised by cost, high frequency of dosing and side effects. 14 Use of some antihypertensive medication may even precipitate the clinical onset of diabetes, 15 making the use of non-pharmacological treatment even more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, studies evaluating data from those with hypertension-obtained from various sources such as national survey data, epidemiologic studies, ambulatory care practices, and high-risk patients-report a varying rate of hypertension control ranging from 29% to 50%. 4,[8][9][10][11][12][13][14][15][16][17] Medication nonadherence is cited as the primary cause for lack of hypertension control. 5,18 Medication nonadherence is defined as the failure to adhere to medication instructions, either willfully or inadvertently.…”
Section: Morisky Medication Adherence Scale (Mmas)mentioning
confidence: 99%